Tensiomyography: from muscle assessment to talent identification tool - Čular, Dražen; Babić, Matej; Zubac, Damir; Kezić, Ana; Macan, Iva; Peyré-Tartaruga, Leonardo Alexandre; Ceccarini, Francesco; Padulo, Johnny (Frontiers in Physiology, 2023)
Tensiomyography (TMG) is a non-invasive and cost-effective tool that is gaining popularity in fields such as sports science, physical therapy, and medicine. In this narrative review, we examine the different applications of TMG and its strengths and limitations, including its use as a tool for sport talent identification and development.In the course of crafting this narrative review, an exhaustive literature search was carried out.Our exploration spanned several renowned scientific databases, such as PubMed, Scopus, Web of Science, and ResearchGate. The materials we sourced for our review included a broad spectrum of both experimental and non-experimental articles, all focusing on TMG. The experimental articles featured varied research designs including randomized controlled trials, quasi-experiments, as well as pre-post studies. As for the non-experimental articles, they encompassed a mix of case-control, cross-sectional, and cohort studies. Importantly, all articles included in our review were written in English and had been published in peer-reviewed journals. The assortment of studies considered provided a holistic view of the existing body of knowledge on TMG, and formed the basis of our comprehensive narrative review.A total of 34 studies were included in the review, organized into three sections: a) assessing muscle contractile properties of young athletes, b) using TMG in the talent identification and development process and c) Future research and perspectives. According to data presented here,the most consistent TMG parameters for determining muscle contractile properties are radial muscle belly displacement, contraction time, and delay time. Biopsy findings from the vastus lateralis (VL) confirmed TMG as a valid tool for estimating the ratio of myosin heavy chain (MHC-I).3TMGs ability to estimate the ratio of %MHC-I has the potential to aid in the selection of athletes with the muscle characteristics best suited for a particular sport, eliminating the need for more invasive procedures. However, more research is warranted to fully understand TMG's potential and its reliability when used with young athletes. Importantly, the use of TMG technology in this process can positively impact health status, reducing the frequency and severity of injuries and the duration of recovery, and subsequently can reduce drop out rates among youth athletes.